2009
DOI: 10.1515/hf.2009.075
|View full text |Cite
|
Sign up to set email alerts
|

An improved drying model for highly-impermeable hardwoods

Abstract: Previously reported drying experiments on highly impermeable hardwoods have shown that bell-shaped within-board moisture content profiles develop as drying proceeds, with a change in concavity around the fibre saturation point. However, drying models based on Fick's second law of diffusion with an Arrhenius temperature dependency for the diffusion coefficient predict a parabolic form. The present work showed that the influence of moisture content on the diffusion coefficient must also be considered to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Scientific and technological efforts to improve drying are as old as wood science, but there are still many challenges as demonstrated by the recent literature. Herritsch and Nijdam (2009) suggested an improved drying model for highly impermeable hardwoods. Junior et al (2010) reported on nonsymmetrical drying tests for the assessment of drying behavior of a hardwood difficult to dry.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific and technological efforts to improve drying are as old as wood science, but there are still many challenges as demonstrated by the recent literature. Herritsch and Nijdam (2009) suggested an improved drying model for highly impermeable hardwoods. Junior et al (2010) reported on nonsymmetrical drying tests for the assessment of drying behavior of a hardwood difficult to dry.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale is that the drying rate is likely controlled by moisture diffusion through wood shells, where the MC is below the FSP. The Fickian approach was attractive for the modelling due to its simplicity and ease of numerical solution (Herritsch and Nijdam 2009). Therefore, the diffusive model is suitable for describing the moisture transfer from inside to outside the board.…”
Section: Determination Of Effective Diffusion Coefficientsmentioning
confidence: 99%
“…Herritsch and Nijdam (2009) developed a drying model that includes both the temperature and MC effects on the diffusion coefficient for highly impermeable hardwoods. Using Matlab 7.0, the coupled partial-differential equations were solved.…”
Section: Introductionmentioning
confidence: 99%
“…Three different models (model based on Lui kov's approach, diffusion model, and multiphase model) were developed and compared for high temperature drying by Kocaefe et al (2007); but the comparison was limited in drying below fiber saturation point (FSP). Herritsch and Nijidam (2009) proposed an improved drying model for highly-impermeable hardwoods in which MC, temperature, and diffusion coefficient were taken into consideration for drying model development for various timber thicknesses under different drying conditions. Zhu and Kaliske (2011) discussed the interrelationship between temperature, MC, and gas pressure by solving partial differential equations (PDEs) under Neumann boundary conditions for both temperature and MC and Dirichlet boundary condition for gas pressure.…”
Section: Introductionmentioning
confidence: 99%